STUDY OF LOMASHATHANA YOGAS IN THE MANAGEMENT OF HIRSUTISM - A CRITICAL REVIEW - Yadav Seema; R. Vidyanath (International Journal of Applied Ayurved Research, 2018)
Though beauty conscious exist in human beings since Vedic period, it is increasing day-by-day in the recent past. It seems to be smooth and unblemished skin and hair boosts the confidence and self-esteem of an individual. Due to change in the life style, many a number of IT professionals and others are facing hair problems particularly either loss of hair or growing of unwanted hair. Hirsutism is defined as the presence of terminal coarse hair in females in a male-like distribution at sides of the face, upper lip, chin, upper back, shoulders, sternum, and upper abdomen. It affects around 5-10% of women and is a common presenting complaint in the dermatological outpatient department (OPD) for cosmetic reasons. Currently many a number of epilation methods are available such as plucking, shaving, threading, waxing, electrolysis, laser therapy etc. These hair removal methods may cause complications like skin inflammation, minor burns, lesions, scarring etc. and some are highly expensive. Keeping this in view a critical study has been carried out to explore the treasure of ancient epilation methods and formulations mentioned in the Ayurvedic literature for the benefit of ailing patients. The study also will be useful for the practitioners as well as research scholars to come out with a safe and cost effective solution for the management of Hirsutism with simple and easily adopting ancient techniques.